Proceedings of the Seventh International Scientific Conference “Intelligent Information Technologies for Industry” (IITI’23) Volume 2 - Kovalev, Sergey; Kotenko, Igor; Sukhanov, Andrey (Lecture Notes in Networks and Systems, 2023)
XIV, 348 p. 134 illus., 93 illus. in color.